Analisis Kepatuhan Koperasi Syariah Pada Implementasi Akad IMBT Ditinjauan dari Fatwa DSN MUI No. 27 Tahun 2002 - Amrullah, Muhammad Ilham; Sholahuddin, Muhammad; Rizka, Rizka (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Essentially, the majority of people want to fulfill their needs for consumer or productive goods quickly and through a simple process, In this context, Islam is present as a solution for society to meet society's needs for assets through financing agreements contract al-Ijarah Muntahiyah Bi at-Tamlik (IMBT). Which aims to review the suitability of the implementation of the contract al-Ijarah Muntahiyah Bi at-Tamlik against DSN-MUI fatwa no. 27 of 2002 about IMBT. Field research is the form of research used, and the research method employed is a descriptive method with a qualitative research paradigm approach. Data was obtained through several data collection techniques, namely observation, interviews and documentation. The data analysis technique used is the Miles and Huberman analysis technique. The results of the research state that apart from the conformity of several IMBT contract implementations to the DSN-MUI Fatwa, The DSN-MUI Fatwa is not followed in a number of implementations, including the transfer of ownership at the start of the IMBT contract, the full tenant-borne maintenance costs for the rental items, and the initial intention of customers applying for IMBT contract financing, which was not to satisfy their needs for consumer or productive goods.